TOURIST CHARACTERISTICS IN FRANCE - Solene ROUX; Estalle Giet (Journal of Applied Sciences in Travel and Hospitality, 2019)
Tourists in France force actors and territories to adapt to the demand and needs of visitors from different countries and cultures. This intercultural requirement requires, in particular, a more detailed knowledge of the practices, perceptions and feelings of foreign tourists, particularly Chinese tourists, whose numbers are increasing sharply in France, Europe and the world. The article proposes an exploratory approach to the representations associated with these practices in France through the use of websites and our teaching at the university over the past 3 years and leads to a first typology. The protocol for analysing tourist practices developed for this example makes it possible to understand the level of tourist satisfaction, to analyses what shapes their complex behaviour based on their feelings on the spot, to better characterise the tourist experience in the broad sense and to imagine a model. From a more operational point of view, the approach makes it possible to envisage an improvement in the dialogue between tourist operators and end users, a finer adaptation of supply and demand, an improvement in the well-being of tourists and a strengthening of the attractiveness of the territories.